Analysis of Meshing Performance for Equal Base Circle Bevel Gear - He Xin; Cao Xuemei (Jixie chuandong)
In order to analyze the bearing capacity and transmission performance of equal base circle bevel gear under actual working conditions, the tooth contact analysis （TCA）is performed to simulate the tooth surface contact pattern and transmission error. Without errors of installing，the modification of tooth line and tooth profile of bevel gear is carried out, the influence of modification parameters of tooth line and tooth profile on transmission error of bevel gear and change of contact area of tooth surface are analyzed. By adjusting the modification parameters to improve the meshing characteristics of the gears，realize better lubricating performance and transmission stability. By machining and rolling a pair of modified equal base bevel gears，the correctness of TCA modification program is verified. The theoretical and experimental basis for the meshing performance analysis of gear is provided.